Design and implementation of three-phases energy storage system using DSP F28379D for laboratory research - Hoai Phong Nguyen; Thuan Thanh Nguyen; Minh Phuong Le; Minh Tan Tran; Cong Duy Pham (HardwareX, 2025)
This paper presents the hardware design for a three-phases energy storage system connected to the grid through a safe isolation transformer, suitable for use in university laboratory experiments. The power hardware configuration includes a bidirectional DC/DC buck-boost converter and a bidirectional 3-phase 6-switch DC/AC converter. Additionally, the control board uses the Texas Instruments DSP F28379D with a charging-discharging control program written in C programming language and compiled with Code Composer Studio (CCS v12). The current and voltage sensing circuits use Hall-effect sensors to isolate the power circuit from the control circuit. A unique aspect of this research is the modular design, allowing for quick and easy upgrades and changes to the configuration and power capacity, facilitating the testing of control algorithms for the storage system. Experiments were conducted on a 3-phase 380(V) power grid through an isolation transformer and a simulated battery bank powered by the APS1000 amplifier, with a 100(V) output voltage controlled in charging mode from the grid and discharging mode to the grid at a controlled power of 230(W). The results show that the hardware model can be used effectively in laboratory settings to serve educational needs.